PERAN KADER DALAM PENGENDALIAN HIPERTENSI - Astriani; Leni Wijaya (LPPM STIKes Mitra Adiguna, 2026)
Hypertension is one of the Non-Communicable Diseases (NCDs) whose prevalence continues to increase and is at risk of causing serious complications to death. Efforts to control hypertension in the community can be done through the empowerment of Posbindu PTM cadres. This study aims to determine the role of cadres in controlling hypertension at Sungai Lumpur Health Center in 2025. This study uses quantitative methods with a descriptive survey approach. The sample in this study were all cadres of Posbindu PTM totaling 56 people, who were selected using total sampling technique. The instrument used in this study was a closed questionnaire. The results showed that 54 cadres (96.4%) had a role that was classified as moderately active, while 2 cadres (3.6%) showed a less active role. The involvement of cadres is reflected in activities such as data collection of residents at risk of hypertension, counseling on hypertension prevention, and routine implementation of posbindu. These results indicate that posbindu cadres have a fairly active role in controlling hypertension. Cadres are expected to increase active participation in all hypertension control activities to support program effectiveness, and play an active role in the five main functions, namely as coordinators, mobilizers, monitors, counselors, and recorders in the implementation of routine posbindu activities.